Strategies for fabricating versatile carbon nanomaterials from polymer precursors. (November 2019) - Le, Thanh-Hai; Yoon, Hyeonseok
Abstract: There has been a continuous pursuit toward developing techniques used to prepare enhanced carbon nanomaterials over the last several decades. In particular, the demand for new and advanced carbon nanomaterials is related to the need to optimize their physicochemical characteristics for specific applications. In this regard, polymer precursors have great potential for fabricating nanostructured carbons with desirable properties since the chemical structure and surface/interface properties of the polymer can be designed and tailored during the preparation process. Various types of polymers including synthetic polymers, natural polymers, and biomass have been investigated as carbon precursors. Elaborate efforts have been made to prepare polymer nanoparticles, polymer blends, and nanocarbon/polymer hybrids for versatile carbon nanomaterials via heat treatment processes, for which knowledge and technologies regarding the interface and polymer chemistry/physics are required. In addition, more in-depth studies into the carbonization mechanism may lead to various strategies for creating advanced carbon nanomaterials with desirable properties. Graphical abstract: Image 1